Inventarisasi Jenis Dan Indeks Ekologi Amfibi (Ordo Anura) Di Kawasan Konservasi Bukit Tangkiling Palangka Raya: Inventory and Ecological Index of Amphibian (Ordo Anura) in the Tangkiling Hill Conservation Area, Palangka Raya - Octavianus, Robby; Hastari, Belinda; Saputra, Aji Eka (HUTAN TROPIKA, 2024)
The purpose of this study (a) inventory and identify the composition of amphibians of the Anura order in the Tangkiling Hill Conservation Area, Palangka Raya City; and (b) calculate the ecological index of the Anura order amphibians in the Tangkiling Hill Conservation Area, Palangka Raya City. The results showed that the number of individuals of the amphibians of Anura order found in the research location was 234 individuals consisting of 18 species from 5 families, with the number of amphibian species found in water was 69.23% while in land 30.76%. Based on the calculation of the ecological index, it was found that the value of the species diversity index (H') was around 1.16 – 2.26 which categorized as "low" to "medium". The value of the species evenness index (E') was found to be 0.5 - 0.75, which is included in the "medium" to "high" category. The abundance index value (D) was found to be around 1.41 – 39.66. Meanwhile, the calculation of the important value index obtained an index value around 3.87 – 23.99 with Limnonectes finchi  having the highest value and Bufo juxtasper, Bufo quadriporcatus, Pseudobufo subasper, and Rana chalconota having the lowest value.